Changes and continuities in the Indigenous perceptions and politicaldemands about their territory: the case of the Indigenous Peoples ofthe Peruvian Amazon region - Espinosa, Óscar (2010)
This article explores changes and continuities in political demandsconcerning territorial rights as they have been articulated byindigenous organizations of the Peruvian Amazon over recentdecades. Its main objective is to demonstrate how particular historicalconjunctures have influenced the ways in which these groups havefocused their efforts in defense of what they consider to be a crucialelement of their way of life, increasingly threatened by incursionsfrom modern society, capitalism and processes of globalization. Theanalysis rejects depictions of the indigenous peoples as passive, opento manipulation by outside interests. At the same time, it provides amore profound understanding of the changes that are taking placewithin indigenous societies with respect to their perception of, andrelationship to, their territories.